Practices and Meanings of Deep Learning in Social Studies Instruction at the Remote Manis Mata School - Joni Iskandar; Siswandi (Yayasan Ilomata, 2026)
Social studies (IPS) learning in remote elementary schools remains constrained by limited access, inadequate infrastructure, and an exam-oriented assessment culture, often resulting in surface-level understanding. Concurrently, curricular orientations promoted by the Kementerian Pendidikan, Kebudayaan, Riset, dan Teknologi Republik Indonesia through the Merdeka Curriculum emphasize contextual social literacy and the development of students’ civic-cultural identity. In this study, identity is defined as the integration of local (inland) cultural belonging and civic awareness, positioning IPS as a medium for socially situated meaning-making and participatory citizenship. This study investigates the practices and meanings of deep learning in IPS classrooms in Manis Mata District, West Kalimantan. Deep learning is operationalized as meaningful conceptual engagement, critical reflection on social realities, and the integration of students’ lived experiences into knowledge construction. Employing a qualitative case-study design, the research was conducted in three remote elementary schools. Data were collected through in-depth interviews, classroom observations, and document analysis involving 6 teachers, 27 upper-grade students, and 3 school leaders. Participants were purposively selected, and data were analyzed thematically. Findings indicate that deep learning becomes meaningful when instruction is rooted in local contexts, although its implementation is shaped by structural constraints. IPS classrooms also function as spaces for civic-cultural identity formation and social awareness, including emotional ambivalence when marginal experiences are expressed. This study refines social constructivist perspectives by highlighting the role of local epistemologies in shaping deep learning within marginalized settings, and suggests the need for contextual teacher development, adaptive assessment, and locally grounded curricula.